Обоснование эффективных схем макроциклов подготовки юных десятиборцев - Максименко, Г.; Maksymenko, G. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
В настоящее время достаточно актуальной является проблема оптимизации подготовки юных десятиборцев в макроциклах. Цель исследования состояла в выявлении эффективных схем построения годичных циклов юных десятиборцев. Методы исследования – теоретический анализ и обобщение, педагогическое наблюдение, тестирование и педагогический эксперимент. В статье представлены результаты исследований по выявлению оптимального соотношения различных по направленности объёмов нагрузок в годичном цикле тренировки юных десятиборцев Presently, a problem of optimization of long-term preparation of young decathlon competitors in a year cycle of training is topical. The purpose of the research is to define an effective scheme of a year cycle of young decathlon competitor’s training. The methods used in the study are: theoretical analysis, generalization and pedagogical observation, pedagogical testing, pedagogical experiment. The research results on optimum ration of loads of different kind in a year cycle of training for young decathlon sportsmen are presented in the article.
Reasoning of Effective Cycle of Training for Decathlon Competitors on the Specialized Basic Level.
Keywords: десятиборцы; объемы нагрузок; тесты; быстрота; сила; скоростно-силовые качества; выносливость; decathlon competitors; scope of loads; speed; power; speed and power skills of sportsmen; endurance